(untitled) (Global Journal of Human-Social Science, 2020)
Security is necessary for a stable democracy as well as flourishing development. Security challenges are prevalent in both developing as well as developed countries. However, a historical as well as recent security challenge in less developed countries suggests a rather interesting picture in comparison to developed countries. This study sought to unravel the security challenges in Ghana and the imperative of Ghana Police Service as a security agency. The mixed-method of data collection was used. The study established that, armed robbery, cybercrime and political vigilantism are the major security challenges in Ghana. It was revealed that, the inefficiency of the police is as results of political interference, lack of logistics, poor condition of service like accommodation, unfair treatment of junior officers among others. The insight gained led to the following recommendations: depoliticizing the police institution, upgrading their system to enhance effective communication, organization of periodic refresher courses among others.